2017
DOI: 10.19082/6002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Entonox for pain management in labor: A systematic review and meta-analysis of randomized controlled trials

Abstract: Background and aimEntonox was one of the important methods for pain management in the delivery process. In previous years some studies have assessed the effect of this method in Iran. In this regard, the aim of this study was to systematically review studies addressing the effect of Entonox for pain management in labor.MethodsThis systematic review and meta-analysis study was conducted in 2016. The required data was collected using keywords such as ”Entonox”, “nitrous oxide”, ”vaginal delivery”, ”pain relief”,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 28 publications
(18 reference statements)
1
4
0
Order By: Relevance
“…12 A meta-analysis by Sheyklo et al showed that the satisfaction rate of the mothers in the Entonox group was 57.6% as compared to 21.3% of mothers in the oxygen group showing a high level of satisfaction. 13 The duration of the active phase of labor in the Entonox group was comparable to the oxygen group in our study. Results of a study by Attar et al revealed that patients in the Entonox group experienced less pain (p ≤ 0.001) as compared to the oxygen group and also had less duration of delivery (p ≤ 0.001).…”
Section: Discussionsupporting
confidence: 70%
“…12 A meta-analysis by Sheyklo et al showed that the satisfaction rate of the mothers in the Entonox group was 57.6% as compared to 21.3% of mothers in the oxygen group showing a high level of satisfaction. 13 The duration of the active phase of labor in the Entonox group was comparable to the oxygen group in our study. Results of a study by Attar et al revealed that patients in the Entonox group experienced less pain (p ≤ 0.001) as compared to the oxygen group and also had less duration of delivery (p ≤ 0.001).…”
Section: Discussionsupporting
confidence: 70%
“…Systematic review and meta-analysis on nitrous oxide for the management of labor pain reported that only few studies of good or fair quality have been published, and the control groups were very heterogeneous [ 2 ]. The review concluded that further research is needed across all of the areas examined: effectiveness, satisfaction, and adverse effects [ 2 , 3 ]. Accordingly, we conducted this study aimed mainly to compare visual analog scores of labor pain and satisfaction levels between women who received nitrous oxide (Entonox ® ) and those who received meperidine, and also to compare the neonatal outcomes, labor courses, and cesarean section rate between both groups.…”
Section: Introductionmentioning
confidence: 99%
“…It can reduce the use of pethidine during labor pain without significant increase in maternal and neonatal complications. [12][13][14][15] Another study found that colonoscopy patients using Entonox felt no more discomfort than those sedated intravenously. Entonox was not associated with a reduction in colonoscopy quality, and patients who received Entonox recovered more rapidly than patients who received intravenous sedation.…”
Section: Discussionmentioning
confidence: 99%